2012
DOI: 10.1177/1354856512441151
|View full text |Cite
|
Sign up to set email alerts
|

Locative journalism: Designing a location-dependent news medium for smartphones

Abstract: This article provides an account of the tensions between locative context-awareness and the act of writing journalistic copy for a mobile application. Based on the field trials of the interdisciplinary LocaNews project, the article discusses locative media's potential for spatially sensitive news journalism.In 2009 researchers in Norway made a medium design called LocaNews, and tested it out with pre-planned procedures for the two fundamental activities: production and reception. Of those who participated, 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 16 publications
0
23
0
5
Order By: Relevance
“…At the same time they had a problem identifying this as journalism, rather than an information service. Nyre et al (2012) discuss the design of LocaNews as a news medium and conclude that it is easier to design a new medium than to establish a new journalistic practice.…”
Section: Methodsmentioning
confidence: 98%
“…At the same time they had a problem identifying this as journalism, rather than an information service. Nyre et al (2012) discuss the design of LocaNews as a news medium and conclude that it is easier to design a new medium than to establish a new journalistic practice.…”
Section: Methodsmentioning
confidence: 98%
“…Few people were able to understand how to view the news through this location format and the reporters had issues in categorizing and classifying news to a specific location. Nyre et al (2012) had three versions of stories in the digital tool categorized by "here," "nearby," and "far" to tie to three aspects of proximity. Nyre et al (2012) stated they had challenges in setting up criteria for the reporters to know which of the three categories to choose when marking the location for a story and for the readers to understand which category to view from depending on where they were.…”
Section: Mobile Technology Studiesmentioning
confidence: 99%
“…Nyre et al (2012) had three versions of stories in the digital tool categorized by "here," "nearby," and "far" to tie to three aspects of proximity. Nyre et al (2012) stated they had challenges in setting up criteria for the reporters to know which of the three categories to choose when marking the location for a story and for the readers to understand which category to view from depending on where they were. The researchers concluded that it was easy to build the digital tool but harder to change journalistic practice.…”
Section: Mobile Technology Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ett område som utforskats är exempelvis s.k. locative journalism, där nyheter knyts samman med plats (Nyre, Bjornestad, Tessem & Vaage Oie, 2012). Andra viktiga områden är s.k.…”
Section: Innehållunclassified